this is what i need to find out: Solve for the x and y intercepts for the rule: (x-6) (x+3)
Roman's answer is correct. Assuming of course that (X - 6)(X + 3) = Y
this is what i need to find out: Solve for the x and y intercepts for the rule: (x-6) (x+3)
Roman's answer is correct. Assuming of course that (X - 6)(X + 3) = Y
If you want the x intercepts of the equation y = (x - 6)(x + 3) then here they are.
X-intercepts:
Set y = 0 and use the zero product property (if ab = 0 then a = 0 or b = 0)
(x - 6)(x + 3) = 0
x - 6 = 0 or x + 3 = 0.
x = 6 or x = -3
Y-intercept:
Set x = 0.
y = (0 - 3)(0 + 6) = -3*6 = -18